Role of skeletal muscle lipids in the pathogenesis of insulin resistance of obesity and type 2 diabetes - Gilbert, Marc (Journal of diabetes investigation, 2021)
ABSTRACT Obesity predisposes individuals to the development of insulin resistance, which is a risk factor for type 2 diabetes, and muscle plays a central role in this phenomenon. Insulin resistance is associated with: (i) a metabolic inflexibility characterized by a reduced impaired switching from free fatty acid (FA) to carbohydrate substrates; and (ii) an ectopic accumulation of triglyceride in skeletal muscle, generating a cellular “lipotoxicity”, but triglyceride per se, does not contribute to insulin resistance (“athlete’s paradox”). A large body of evidence supports the idea that a decreased mitochondrial capacity to oxidize FA leads to an accretion of intracellular triglyceride and an accumulation of acyl‐CoAs, which are used to synthesize diacylglycerol and ceramide. These lipid derivatives activate serine kinases, leading to increase of insulin receptor substrate 1 serine phosphorylation, which impairs insulin signaling. A second model proposes that insulin resistance arises from an excessive mitochondrial FA oxidation. Studies have shown that the type of FA, unsaturated or saturated, is critical in the development of insulin resistance. It should be also stressed that FA oversupply activates inflammatory signals, induces endoplasmic reticulum stress, increases mitochondrial oxidative stress and influences the regulation of genes that contributes to impaired glucose metabolism. These cellular insults are thought to engage stress‐sensitive serine kinases disrupting insulin signaling. In conclusion, reduced dietary lipid intake in association with physical exercise could be a therapeutic option to improve insulin sensitivity. Obesity predisposes individuals to the development of insulin resistance, which is a risk factor for type 2 diabetes, and muscle plays a central role in this phenomenon. The insulin resistance is related to impaired mitochondrial oxidation of fatty acids, resulting to an accumulation of lipid derivatives, which in turn decrease insulin sensitivity. However, excessive mitochondrial fatty acid oxidation might also lead to impaired insulin effect.